PENGARUH MEDIA BOARD GAME TERHADAP NILAI AGAMA DAN MORAL ANAK USIA 5-6 TAHUN DI KB TK BINTANG CENDEKIA KECAMATAN TAMPAN KOTA PEKANBARU - Salmiati, Salmiati; Chairilsyah, Daviq; N, Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: Based on the first observation on the religious and moral values of children age 5-6 years at KB TK Bintang Cendekia, at Tampan, Pekanbaru, it was found that the students religious and moral values did not develope optimally. Therefore, it is important to do a research towards students religious values and their morals by using board game media. The purpose of this study is to examine the effect of Board Game media on the religious and moral values of children aged 5-6 years. This research was conducted at KB BintangCendekia Kindergarten, Tampan District, Pekanbaru City for observation and research on February 2019 to July 2019. The study used an experimental method with one group pre-test post-test design with a sample of 15 children. Data collection techniques used in this study were to use observation sheets of children's religious and moral values. The data analysis technique used t-test using I.BM SPSS statistical version 20.From the results of data analysis, the t-count is 24,450, greater than t-table = 2,145 with sig 0,000 <0,05. It can be concluded that there are significant differences in children's religious and moral values before and after the use of Board Game media. Based on the results of the hypothesis test, there is an influence of the Board Game media on the religious and moral values of children aged 5-6 years at the KB Cendekia Kindergarten KB, Tampan District, Pekanbaru City by 72.94%.Key Words: Board Game Media, Religious and Moral Values